Poor Embryo Quality Is Associated With A Higher Risk of Low Birthweight in Vitrified-Warmed Single Embryo Transfer Cycles - Huang, Jiaan; Tao, Yu; Zhang, Jie; Yang, Xiaoyan; Wu, Jiayi; Kuang, Yanping; Wang, Yun (Frontiers in Physiology, 2020)
Background Previous studies have reported the association between embryo quality and perinatal outcomes in fresh cycles, after cleavage-stage or blastocyst embryo transfer, and found no significant difference. However, in terms of vitrified-warmed embryo transfer cycles, the impact of embryo quality on neonatal and maternal outcomes has not been evaluated. Objectives To explore the association between the quality of a single vitrified-warmed embryo and perinatal outcomes. Methods This retrospective study included 2403 live-born singletons derived from single vitrified-warmed embryo transfer cycles during January 2006 and July 2018. Neonatal and maternal outcomes were compared between singletons resulting from the use of single good quality embryo (GQE) (n = 1854) and single poor quality embryo (PQE) (n = 549) and analyzed in the group of cleavage-stage embryo transfer and the group of blastocyst transfer, respectively. Results A significantly higher risk of low birthweight (LBW, birthweight <2500 g) was observed in the singletons derived from the transfer of single PQE compared with those derived from the transfer of single GQE both in cleavage and blastocyst stages (cleavage-stage, AOR 2.62, 95% CI 1.27–5.37; blastocyst stage, AOR 1.98, 95% CI 1.06–3.70). An increased risk of preterm birth (PTB, gestational age <37 weeks) was also observed in singletons born after transfer of a PQE of cleavage-stage compared with those after a GQE of cleavage-stage (AOR 2.40, 95% CI 1.28–4.49). The transfer of single poor quality blastocyst was associated with a higher risk of placenta previa compared with the transfer of single good quality blastocyst (AOR 2.65, 95% CI 1.26–5.57). Other maternal complications, neonatal malformations, and neonatal complications were similar between compared groups. Conclusion In vitrified-warmed cycles with single embryo transfer, poor embryo quality would result in a significantly higher risk of LBW, regardless of cleavage-stage or blastocyst embryo transfer. Meanwhile, the transfer of poor cleavage-stage embryo was also associated with an increased incidence of PTB.